Solution of the problem of contact of a punch with multiply connected half-plane - Lysenko (Zvyozdochkina), Elena; Lysenko, Valentin (My University, 2004)
This paper is devoted to solving of problems about smooth contact of a punch with multiply connected half-plane. Half-plane contains a square hole different sizes. The solution is obtained with help of a new analytically-numerical approach, which based on synthesis of a method of boundary elements and analytical solutions for half-plane. Researches of the contact stresses under a punch are presented.
Keywords: integral presentations; Method of Boundary Elements; bounding contour; punch; contact stresses; strainly-deformed state; интегральное представление; метод граничных элементов; ограничивающий контур; штамп; контактные напряжения; напряженно-деформируемое состояние; інтегральне представлення; метод крайових елементів; обмежуючий контур; контактні напруження; напружено-деформівний стан; кафедра економіки праці та менеджменту